Novel benzyl acrylate neutron / gamma discrimination plastic scintillator and preparation method thereof

By using materials such as benzyl acrylate and dyes, combined with gradient polymerization technology, a new plastic scintillator was prepared, which solved the problems of high preparation cost, long molding time and insufficient brittleness in the prior art, and achieved efficient neutron/gamma identification and good mechanical properties.

CN119592000APending Publication Date: 2025-03-11XIANGTAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411907567.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing plastic scintillators have high preparation costs, long forming time, high brittleness, and limited neutron/gamma identification capabilities.

Method used

Benzyl acrylate is used as a polymer matrix, combining crosslinking agent, initiator, main fluorescent dye and secondary fluorescent dye to prepare a new plastic scintillator through gradient polymerization.

Benefits of technology

It shortens the forming time, improves the brittleness of the plastic scintillator, reduces the preparation cost, improves the neutron/gamma identification ability, and has good light transmittance, light yield, stability and hardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592000A_ABST
    Figure CN119592000A_ABST
Patent Text Reader

Abstract

The invention discloses a novel benzyl acrylate neutron / gamma discrimination plastic scintillator and a preparation method and application thereof. The plastic scintillator is composed of a polymer matrix, a main fluorescent dye and a secondary fluorescent dye, the polymer matrix is benzyl acrylate (BA), the main fluorescent dye is 2, 5-diphenyl oxazole (PPO), and the secondary fluorescent dye is 7-diethylamino-4-methylcoumarin (MDAC) or 9, 10-diphenyl anthracene (DPA). The prepared plastic scintillator uses a new organic polymer matrix, and compared with a plastic scintillator of the same type, the preparation cost is lower, the forming time is shorter, and the plastic scintillator has good stability, optical transparency and mechanical strength and has neutron-gamma discrimination capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel benzyl acrylate-based plastic scintillator for neutron / gamma discrimination and a preparation method and application thereof, and belongs to the field of nuclear technology radiation detection. Background Art

[0002] In radiation fields that produce mixed pulses of neutrons and gamma rays such as nuclear physics experiments, spallation neutron sources, nuclear fission / fusion reactors, and nuclear astronomical processes, neutron detection and neutron / gamma discrimination are of great significance for monitoring the neutron energy spectrum and neutron beam intensity. Currently, existing commercial scintillators are difficult to meet the application requirements in various physical fields. They have the disadvantages of limited neutron / gamma discrimination capabilities, insufficient mechanical strength and optical transparency. Therefore, it is of great practical significance to develop new neutron / gamma discrimination scintillator detectors with high sensitivity detection and high optical transparency. The discrimination of neutrons and gamma rays is directly related to the accuracy and efficiency of neutron flux and energy spectrum measurement. People began to study this issue as early as the late 1950s.

[0003] Plastic scintillators are mainly composed of matrix materials and scintillating materials. They have good mechanical properties and can be processed into any shape. They are non-toxic, not easy to deliquesce and oxidize, and are resistant to radiation. They are suitable for various harsh environments. Plastic scintillator detectors made by special processes can discriminate neutrons and gamma rays. At present, the most successful plastic scintillator with neutron / gamma discrimination effect is developed by the Livermore National Laboratory in the United States. The neutron / gamma discrimination ability of the plastic scintillator made by Zaitseva et al. in this laboratory has exceeded the commercial liquid scintillator EJ-309. Based on the relevant technology of Livermore National Laboratory, Eljen Technology Company in the United States produces and sells EJ-299 and improved EJ-276 plastic scintillators with high neutron / gamma discrimination ability. However, there has been no report on the successful development of plastic scintillators with ideal neutron / gamma discrimination effect in China. Traditional plastic scintillators are mainly based on polystyrene or polymethylstyrene as matrix materials, but the use of these materials to prepare scintillators generally has problems such as long polymerization time and brittle fracture. Therefore, we can use a new matrix and hopefully develop a new type of plastic scintillator with short polymerization time, low cost, high transparency / mechanical strength, and the ability to perform neutron / gamma discrimination. Summary of the invention

[0004] In view of the high preparation cost, long molding time and excessive brittleness of existing plastic scintillators, the purpose of the present invention is to provide an organic plastic scintillator component with low preparation cost and short molding time, forming a new plastic scintillator with neutron / gamma discrimination capability and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The invention discloses a novel benzyl acrylate-based neutron / gamma discrimination plastic scintillator, which is composed of a polymer matrix, a crosslinking agent, an initiator, a primary fluorescent dye and a secondary fluorescent dye. The polymer matrix is ​​benzyl acrylate (BA), the crosslinking agent is divinylbenzene (DVB), the initiator is azobisisobutyronitrile (AIBN), the primary fluorescent dye is 2,5-diphenyloxazole (PPO), and the secondary fluorescent dye is 7-diethylamino-4-methylcoumarin (MDAC) or 9,10-diphenylanthracene (DPA).

[0007] The neutron / gamma discrimination plastic scintillator of the present invention uses benzyl acrylate as an organic matrix. The inventors have found that using benzyl acrylate as the scintillator matrix shortens the molding time and improves the brittleness of the plastic scintillator. The prepared scintillator has good transparency and neutron / gamma discrimination capability.

[0008] Primary fluorescent dyes play a vital role in plastic scintillators. They are key components that enable plastic scintillators to convert high-energy radiation into visible light. Primary fluorescent dyes are usually some organic compounds, such as 2,5-diphenyloxazole (PPO), which have strong spin-orbit interactions and can achieve energy transfer from the matrix to the electronic energy levels in its molecules. When the plastic scintillator is excited by radiation, PPO absorbs energy and transitions to an excited state, and then emits light when it returns to the ground state. The fluorescence emission peak of PPO is at 365nm, which enables the plastic scintillator to emit strong fluorescence near this wavelength. Therefore, the present invention uses PPO as the main fluorescent dye and explores its effect on the performance of the scintillator from low concentration to high concentration. In order to avoid the self-absorption effect caused by high concentrations of primary fluorescent dyes, a small amount of secondary fluorescent dyes are usually introduced. These secondary fluorescent dyes can absorb the fluorescence emitted by the primary fluorescent dye and emit fluorescence at a longer wavelength, thereby weakening the self-absorption effect and improving the transmission efficiency of light.

[0009] Through a large number of experiments, the present invention uses benzyl acrylate as a matrix, selects PPO as a main fluorescent dye, and MDAC / DPA as a secondary fluorescent dye to prepare a plastic scintillator. The present invention provides a new type of plastic scintillator, which has neutron / gamma discrimination capability, short molding time, and good light transmittance, light yield, stability and hardness.

[0010] In a preferred embodiment, the polymer matrix is ​​entirely benzyl acrylate.

[0011] The inventors found that when benzyl acrylate is selected as the organic polymer matrix, the final prepared new plastic scintillator has the shortest molding time and the best neutron / gamma discrimination ability.

[0012] In a preferred embodiment, the mass fraction of the primary fluorescent dye PPO in the novel neutron / gamma discrimination plastic scintillator is 10-30 wt.%, and the mass fraction of the secondary fluorescent dye MDAC / DPA in the novel neutron / gamma discrimination plastic scintillator is 0.01-0.02 wt.%.

[0013] In a preferred embodiment, the mass fraction of the crosslinking agent DVB in the novel neutron / gamma discrimination plastic scintillator is 5 wt.%, and the mass fraction of the initiator AIBN in the novel neutron / gamma discrimination plastic scintillator is 0.05 wt.%.

[0014] The inventors found that when the mass fraction of the primary fluorescent dye PPO is 10-30wt.%, and the mass fraction of the secondary fluorescent dye MDAC / DPA is 0.01-0.02wt.%, the prepared polybenzyl acrylate-based plastic scintillator has good optical transparency and neutron / gamma ray discrimination capability.

[0015] In the present invention, adding an appropriate amount of main fluorescent dye will improve the discrimination ability of the scintillator, but the dosage still needs to be controlled. When the content of the main fluorescent dye is too high, its self-absorption effect is obvious, resulting in reduced luminous efficiency, and samples with excessive PPO will partially precipitate after being placed for a period of time and are difficult to dissolve.

[0016] The preferred solution is to put the precursor solution into a vacuum drying oven after the tube is sealed and prepared at 50°C for 12 hours, then heat it to 75°C at a rate of 10°C / h and heat it for 20 hours; then heat it to 90°C at a rate of 5°C / h and heat it for 10 hours; then cool it to 80°C at a rate of 10°C / h and heat it for 14 hours; then cool it to 50°C at a rate of 8°C / h and heat it for 10 hours, and finally stop the program to let the sample cool down to room temperature in the oven before taking it out. The fully polymerized sample is taken out of the glass tube and polished to obtain the final product.

[0017] The inventors found that in the polymerization process of the present invention, the scintillator prepared by the above gradient has the highest transparency and the best mechanical properties. When the highest temperature of the gradient heating is adjusted to 95°C, the mechanical properties of the obtained plastic scintillator decrease, and the final form is light yellow.

[0018] Principles and advantages

[0019] The present invention uses a new aromatic organic substance benzyl acrylate as a matrix material of a plastic scintillator, shortens the polymerization molding time of the scintillator, reduces brittle fracture, and avoids self-absorption of high-concentration fluorescent dyes by adding a primary fluorescent dye PPO in combination with different secondary fluorescent dyes and selecting a suitable secondary fluorescent dye.

[0020] The energy transfer process of the present invention is as follows: benzyl acrylate is used as an energy donor, the main fluorescent dye PPO is used as a first energy receiver, and the energy is then transferred to the second energy receiver MDAC / DPA through PPO, and the final output photons are received and converted by an instrument.

[0021] The advantages of the present invention are: under the action of benzyl acrylate molecules, when different incident particles such as neutrons or gamma rays are incident on the plastic scintillator, they will interact with the atoms in the scintillator. For gamma rays, they mainly interact with electrons through Compton scattering and photoelectric effect; while neutrons interact with atomic nuclei through elastic scattering or inelastic scattering with atomic nuclei. When gamma rays interact with plastic scintillators, Compton scattered electrons are generated, and these electrons move in the scintillator and stimulate fluorescence. Neutrons generate recoil protons through interaction with atomic nuclei, and these recoil protons move in the scintillator and stimulate fluorescence. Since the energy deposition and scintillation light mechanisms generated by neutrons and gamma rays in plastic scintillators are different, the pulse shapes they generate will also be different. The plastic scintillator composed of benzyl acrylate has a short molding time, reduces the synthesis cost, reduces the brittleness of the material, has excellent stability, light transmittance and neutron gamma discrimination ability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 These are sample images of Examples 1, 2, 5, 9, and 10 of the present invention taken under visible light.

[0023] Figure 2 Graphs showing pulse shape discrimination of Examples 1, 2, 5, 9, and 10 of the present invention.

[0024] Figure 3 This is the pulse shape discrimination spectrum of Example 6 of the present invention.

[0025] Figure 4 This is the excitation emission spectrum of Example 5 of the present invention.

[0026] Figure 5 1 and 2 are pulse height spectra of Examples 1, 2, 5, 9 and 10 of the present invention. DETAILED DESCRIPTION

[0027] The preparation of the novel plastic scintillator of the present invention is further described below through specific examples.

[0028] Example 1

[0029] (1) 0.3 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutyronitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 10 wt.%, and the proportion of MDAC was 0.2 wt.%.

[0030] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0031] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 50°C for 12 hours, then the temperature was increased to 75°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 90°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 50°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0032] Example 2

[0033] (1) 0.45 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutylnitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 15 wt.%, and the proportion of MDAC was 0.2 wt.%.

[0034] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0035] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 50°C for 12 hours, then the temperature was increased to 75°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 90°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 50°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0036] Example 3

[0037] (1) 0.45 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutylnitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 15 wt.%, and the proportion of MDAC was 0.2 wt.%.

[0038] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0039] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 45°C for 12 hours, then the temperature was increased to 80°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 95°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 45°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0040] Example 4

[0041] (1) 0.6 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutylnitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 20 wt.%, and the proportion of MDAC was 0.1 wt.%.

[0042] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0043] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 50°C for 12 hours, then the temperature was increased to 75°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 90°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 50°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0044] Example 5

[0045] (1) 0.6 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutylnitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 20 wt.%, and the proportion of MDAC was 0.2 wt.%.

[0046] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0047] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 50°C for 12 hours, then the temperature was increased to 75°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 90°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 50°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0048] Example 6

[0049] (1) 0.6 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 9,10-diphenylanthracene (DPA), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutylnitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / DPA precursor solution, wherein the proportion of PPO was 20 wt.%, and the proportion of DPA was 0.2 wt.%.

[0050] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0051] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 50°C for 12 hours, then the temperature was increased to 75°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 90°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 50°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0052] Example 7

[0053] (1) 0.6 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutylnitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 20 wt.%, and the proportion of MDAC was 0.2 wt.%.

[0054] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0055] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 45°C for 12 hours, then the temperature was increased to 80°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 95°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 45°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0056] Example 8

[0057] (1) 0.75 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutyronitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred in a mass percentage ratio; the stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 25 wt.%, and the proportion of MDAC was 0.1 wt.%.

[0058] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0059] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 50°C for 12 hours, then the temperature was increased to 75°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 90°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 50°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0060] Example 9

[0061] (1) 0.75 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutylnitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 25 wt.%, and the proportion of MDAC was 0.2 wt.%.

[0062] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0063] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 50°C for 12 hours, then the temperature was increased to 75°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 90°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 50°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0064] Example 10

[0065] (1) 0.9 g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), 0.006 g of the wavelength shifter 7-diethylamino-4-methylcoumarin (MDAC), 0.15 g of divinylbenzene (DVB), 0.0015 g of the initiator azobisisobutylnitrile (AIBN) and 3.0 g of benzyl acrylate (BA) were mixed and stirred uniformly according to mass percentage; the uniformly stirred mixed solution was ultrasonically dispersed with the dye molecules to obtain a BA / PPO / MDAC precursor solution, wherein the proportion of PPO was 30 wt.%, and the proportion of MDAC was 0.2 wt.%.

[0066] (2) Add the precursor solution into a glass tube of a customized diameter, and then place the glass tube into a container filled with liquid nitrogen to solidify the precursor solution into a solid; then use a vacuum pump to vacuum it and introduce nitrogen gas, repeat the above treatment five times, and then sinter and seal the tube.

[0067] (3) The sealed glass tube was placed in an oven for gradient reaction. The temperature was kept at 50°C for 12 hours, then the temperature was increased to 75°C at a rate of 10°C / h and kept for 20 hours; then the temperature was increased to 90°C at a rate of 5°C / h and kept for 10 hours; then the temperature was decreased to 80°C at a rate of 10°C / h and kept for 14 hours; then the temperature was decreased to 50°C at a rate of 8°C / h and kept for 10 hours. Finally, the program was stopped to allow the sample to cool to room temperature in the oven before being taken out. The fully polymerized sample was taken out of the glass tube and polished to obtain the final product.

[0068] The following is an analysis of the pulse shape discrimination performance of the new plastic scintillator obtained in Examples 1-10, the excitation emission spectrum

[0069] Figure 2This is the neutron / gamma pulse shape discrimination spectrum of Examples 1, 2, 5, 9, and 10. The distribution of neutron and gamma-ray energy bands can be clearly seen in the spectrum. The upper part is the pulse signal generated by neutrons, and the lower part is the pulse signal generated by gamma rays. The secondary fluorescent dyes used in the samples in this group of data are all MDAC, which shows that this new type of polybenzyl acrylate-based plastic scintillator has neutron-gamma resolution ability.

[0070] Figure 3 This is the neutron / gamma pulse shape discrimination spectrum of Example 6, from which we can also see that this new type of polybenzyl acrylate-based plastic scintillator has neutron / gamma resolution ability, but different secondary fluorescent dyes are used. The compatibility between DPA and PPO is not as good as that between MDAC and PPO, the energy transfer efficiency is relatively low, and the performance is slightly lower than that of Example 5 under the same conditions.

[0071] Figure 4 This is the excitation-emission spectrum of Embodiment 3. As can be seen from the figure, we can observe an excitation peak around 280-300nm, which corresponds to the fluorescence absorption of benzyl acrylate. Two peaks appear at 370nm and 425nm. The peak at 370nm is the characteristic emission peak of the primary fluorescent dye PPO, while the peak at 425nm is the characteristic emission peak of the secondary fluorescent dye MDAC. The characteristic peak of PPO at 370nm is very small, indicating that the energy transfer efficiency is very high in the process of fluorescence energy resonance transfer.

[0072] Figure 5 It is the scintillator pulse height spectrum of implementation modes 1, 2, 5, 9, and 10. Under the 137Cs radiation source, the relative light yield of the polybenzyl acrylate-based scintillator is compared with that of the commercial EJ276. It can be seen that with the increase of the content of the main fluorescent dye PPO, the light yield shows an upward trend, and when the PPO content reaches 25wt.%, its light yield is basically the same as that of EJ276.

[0073] Comparative Example 1

[0074] The other conditions were the same as those in Example 3, except that the temperature was changed by placing it in an oil bath for gradient temperature increase. During the polymerization process, the temperature was unstable and it was not in a vacuum environment, resulting in incomplete polymerization, partial blackening on the bottom, and an unsightly appearance of the sample.

[0075] Comparative Example 2

[0076] The other conditions were the same as those in Example 3. After the sample was cooled to room temperature and taken out from the oven, it was placed in a vacuum drying oven at 50°C for annealing again for two hours to increase its stability. After taking it out, it was found that although the scintillator had good optical transparency, it turned slightly yellow and its performance was reduced.

[0077] Comparative Example 3

[0078] Other conditions were the same as those in Example 3, except that the initiator AIBN was not added. It was found that it could not be cured smoothly, and the precursor swelled into small particles in the test tube. It was taken out as a white solid and could not be tested.

Claims

1. A novel benzyl acrylate-based plastic scintillator with neutron / gamma discrimination capability, characterized in that: The plastic scintillator is composed of a polymer matrix, a primary fluorescent dye and a secondary fluorescent dye, wherein the polymer matrix is ​​benzyl acrylate (BA), the primary fluorescent dye is 2,5-diphenyloxazole (PPO), and the secondary fluorescent dye is 7-diethylamino-4-methylcoumarin (MDAC) or 9,10-diphenylanthracene (DPA).

2. The novel plastic scintillator with neutron / gamma discrimination capability according to claim 1, characterized in that: The plastic scintillator matrix is ​​obtained from benzyl acrylate monomers through free radical polymerization.

3. The novel plastic scintillator with neutron / gamma discrimination capability according to claim 1, characterized in that: The mass fraction of the main fluorescent dye PPO in the neutron / gamma discrimination plastic scintillator is 10-30wt.%.

4. The novel plastic scintillator with neutron / gamma discrimination capability according to claim 1, characterized in that: The mass fraction of the secondary fluorescent dye MDAC / DPA in the neutron / gamma discrimination plastic scintillator is 0.01wt.% to 0.02wt.%.

5. The method for preparing a new type of plastic scintillator with neutron / gamma discrimination capability according to any one of claims 1 to 4, characterized in that The following steps: weigh benzyl acrylate, PPO, MDAC / DPA, DVB, AIBN, etc. to prepare a mixed solution. In order to obtain a high-quality scintillator, the prepared solution needs to be pretreated; the pretreatment is to transfer the solution into a customized glass tube, use a vacuum pump to vacuum it, and introduce nitrogen, repeat the treatment five times and then seal the tube. Then place the glass tube in a vacuum drying oven to perform a polymerization reaction, and finally obtain a new neutron / gamma discrimination plastic scintillator.

6. The method for preparing a novel plastic scintillator with neutron / gamma discrimination capability according to claim 5, characterized in that: The content of benzyl acrylate is 100wt.%, the mass fraction of PPO is 10-30wt.%, the mass fraction of MDAC / DPA is 0.01-0.02wt.%, the mass fraction of AIBN is 0.005wt.%, and the mass fraction of DVB is 5wt.%.

7. The method for preparing a novel plastic scintillator with neutron / gamma discrimination capability according to claim 5, characterized in that: The polymerization reaction process is as follows: keeping the temperature at 30-50°C for 6-12 hours; heating to 70-80°C at a rate of 7-10°C / h and keeping the temperature for 18-20 hours; then heating to 85-95°C at a rate of 3-5°C / h and keeping the temperature for 8-10 hours; then cooling to 70-80°C at a rate of 7-10°C / h and keeping the temperature for 12-14 hours; then cooling to 40-50°C at a rate of 5-8°C / h and keeping the temperature for 6-10 hours, and then naturally cooling to room temperature.

8. The method for preparing a novel plastic scintillator with neutron / gamma discrimination capability according to claim 5, characterized in that: The novel benzyl acrylate-based plastic scintillator is applied to neutron detection in a pulse radiation field mixed with neutrons and gamma rays.

Citation Information

Patent Citations

  • Scintillation composite material for neutron-gamma discrimination and preparation method and application thereof

    CN115902990A

  • Neutron / gamma discrimination plastic scintillator with high fluorescence intensity and high hardness and preparation method and application thereof

    CN117964986A

  • Materials, method, and apparatus for detecting neutrons and ionizing radiation

    US20120241630A1

  • Use of multi-functional cross-linking agents in the manufacture of pulse shape discriminating plastic scintillators, the scintillator, and methods of using the same

    US20190033474A1

  • Scintillation counter and associated manufacturing method

    WO2013076281A1